2009
DOI: 10.1021/ol901361h
|View full text |Cite
|
Sign up to set email alerts
|

Strapped Calix[4]pyrroles Bearing a 1,3-Indanedione at a β-Pyrrolic Position: Chemodosimeters for the Cyanide Anion

Abstract: A strapped calix[4]pyrrole bearing an 1,3-indanedione group at a β-pyrrolic position has been synthesized and studied as a ratiometric cyanide selective chemosensor. A concentration-dependent bleaching of the initial yellow color was observed upon addition of the cyanide anion. The bleaching, which was observed exclusively with the cyanide anion, occurred even in the presence of other anions. Spectroscopic studies provides support for a mechanistic interpretation wherein the cyanide anion forms a complex with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(25 citation statements)
references
References 11 publications
(17 reference statements)
1
24
0
Order By: Relevance
“…Many probes with reversible sensing nature for cyanide ion have been reported in literature . It may be more advantageous if cyanide can be detected and scavenged in an irreversible manner through covalent bond formation between cyanide ion and the sensor . The DCV group, present in 1 b and 2 b was exploited for selective and sensitive detection of aqueous cyanide in DMSO solution of the probes.…”
Section: Introductionsupporting
confidence: 87%
“…Many probes with reversible sensing nature for cyanide ion have been reported in literature . It may be more advantageous if cyanide can be detected and scavenged in an irreversible manner through covalent bond formation between cyanide ion and the sensor . The DCV group, present in 1 b and 2 b was exploited for selective and sensitive detection of aqueous cyanide in DMSO solution of the probes.…”
Section: Introductionsupporting
confidence: 87%
“…The calixpyrroles have been widely studied as both colourimetric 58,61,78,81,88,98 and fluorimetric 61 sensors for a variety of anions, for example as selective sensors for cyanide. The calixpyrroles have been widely studied as both colourimetric 58,61,78,81,88,98 and fluorimetric 61 sensors for a variety of anions, for example as selective sensors for cyanide.…”
Section: Discussionmentioning
confidence: 99%
“…Calix [4]pyrroles that were cis and trans strapped could be synthesised with phthalamide linkers. Formylation of a calix [4]pyrrole strapped with a phthalyl ester unit and condensation of the product with 1,3-indanedione 88 gave two isomeric products, one of which is shown in Figure 5.35b. These materials demonstrated enhanced binding of halides in comparison to unstrapped calixpyrroles but did not show enhancements in selectivity.…”
Section: Strapped Calixpyrrolesmentioning
confidence: 99%
“…10 times larger for the (S)-guest-(S)-host pair than in the case of the corresponding (R)-guest-(S)-host combination. A strapped calix [4]pyrrole bearing an 1,3-indanedione group at a b-pyrrolic position have shown that the system is a good ratiometric cyanide-selective chemosensor (Scheme 10) [72]. A concentration-dependent bleaching of the initial yellow colour was observed upon addition of the cyanide anion.…”
Section: -46mentioning
confidence: 98%